Life history parameters and scale-cover surface area of Aonidiella aurantii are altered in a mating disruption environment: implications for biological control - Vanaclocha, Pilar; Vacas, Sandra; Alfaro, Cristina; Primo, Jaime; Verdú, María J.; Navarro-Llopis, Vicente; Urbaneja, Alberto (2017)
BACKGROUND: In recent years, environmentally safe measures to control the California red scale (CRS), Aonidiella aurantii (Maskell), have been successfully implemented. These measures include mating disruption (MD) and biological control. The goal of this study was to examine the effect of high concentrations of the CRS sex pheromone on its life history parameters and scale-cover surface area under controlled laboratory conditions. RESULTS: The developmental time of both males and females of CRS increased with exposure to airborne pheromone. MD had an effect on both the total number of progeny and on the crawler production period for females. Accordingly, demographic parameters such as net fecundity (R0) and intrinsic rate of increase (rm) were significantly lower in the pheromone-treated populations. The largest scale-cover surface areas were observed in the CRS reared in the pheromone environment. CONCLUSION: A clear influence of airborne pheromone on the biology of CRS has been demonstrated. In addition to the classical mating disruption benefits of this technique, additional benefits, such as increase in the duration of exposure to natural enemies and increase in size, which benefits some species of parasitoids, have been confirmed. Copyright (c) 2012 Society of Chemical Industry